Multiple-peak and single-peak dental curing lights comparison on the wear resistance of bulk-fill composites - Beatriz Ometto Sahadi; Richard Bengt Price; Carolina Bosso André; Maicon Sebold; Gabriel Nima Bermejo; Regina Guenka Palma-Dibb; Juliana Jendiroba Faraoni; Carlos José Soares; Marcelo Giannini (Sociedade Brasileira de Pesquisa Odontológica, 2018)
Abstract: The effects of tooth brushing could affect the long-term esthetic outcome of composite restorations. This study evaluated the effect of two different emission spectrum light-curing units on the surface roughness, roughness profile, topography and microhardness of bulk-fill composites after in vitro toothbrushing. Valo (multiple-peak) and Demi Ultra (single-peak) curing lights were each used for 10s to polymerize three bulk-fill resin composites: Filtek Bulk Fill Posterior Restorative (FBF), Tetric EvoCeram Bulk Fill (TET) and Surefil SDR Flow (SDR). After 30,000 reciprocal strokes in a toothbrushing machine, the roughness profile, surface roughness, surface morphology, and microhardness were examined. Representative SEM images were also obtained. When light-cured with the Demi Ultra, SDR showed the most loss in volume compared to the other composites and higher volume loss compared to when was light-cured with Valo. The highest surface roughness and roughness profile values were found in SDR after toothbrushing, for both light-curing units tested. FBF always had the greatest microhardness values. Light-curing TET with Valo resulted in higher microhardness compared to when using the Demi Ultra. Confocal and SEM images show that toothbrushing resulted in smoother surfaces for FBF and TET. All composites exhibited surface volume loss after toothbrushing. The loss in volume of SDR depended on the light-curing unit used. Toothbrushing can alter the surface roughness and superficial aspect of some bulk-fill composites. The choice of light-curing unit did not affect the roughness profile, but, depending on the composite, it affected the microhardness.